Comparison of midline catheters and peripherally inserted central catheters to reduce the need for general anesthesia in children with respiratory disease: A feasibility randomized controlled trial. Issue 9 (21st June 2021) - Kleidon, Tricia M.; Schults, Jessica A.; Wainwright, Claire; Mihala, Gabor; Gibson, Victoria; Saiyed, Masnoon; Byrnes, Joshua; Cattanach, Paula; Macfarlane, Fiona; Graham, Nicolette; Shevill, Elizabeth; Ullman, Amanda J.
Abstract: Background: The optimal intravenous device for antibiotic administration for children with respiratory disease is uncertain. We assessed the feasibility of a randomized controlled trial comparing midline catheters with peripherally inserted central catheters. Methods: Prospective, two‐arm, feasibility randomized controlled trial in an Australian tertiary, pediatric hospital. Random assignment of 110 children (<18 years) to receive (i) midline catheter and (ii) peripherally inserted central catheters. Primary outcome was feasibility (eligibility, recruitment, retention, protocol adherence, and acceptability), and the primary clinical outcome was general anesthesia requirement for intravenous catheter insertion. Secondary outcomes: insertion time, treatment delays, infusion efficiency, device failure, complications, and cost. Results: There was 80% recruitment, 100% retention, no missing data, and high patient/staff acceptability. Mean patient experience assessed on a 0–10 numeric rating scale was 8.0 peripherally inserted central catheters and 9.0 (midline catheters), respectively. Participant eligibility was not achieved (49% of screened patients) and moderate protocol‐adherence across groups (89% peripherally inserted central catheters vs. 76% midline catheter). Insertion of midline catheter for pulmonary optimization reduced the requirement for general anesthesia compared to peripherally inserted central catheters (10% vs. 69%; odds ratio = 0.01, 95% confidence interval: 0.00–0.09). Midline catheters failed more frequently (18.1 vs. 5.5 peripherally inserted central catheters per 1000 catheter‐days); however, this reduced over trial duration. Midline catheter insertion compared to peripherally inserted central catheters saved AUD1451 per pulmonary optimization episode. Conclusions: An efficacy trial is feasible with expanded eligibility criteria and intensive staff training when introducing a new device. Midline catheter for peripherally compatible infusions is acceptable to patients and staff, might negate the need for general anesthesia and results in significant cost savings.